Sugar activation and glycosylation in Plasmodium. (December 2015) - Cova, Marta; Rodrigues, João; Smith, Terry; Izquierdo, Luis
Abstract Glycoconjugates are important mediators of host-pathogen interactions and are usually very abundant in the surface of many protozoan parasites. However, in the particular case of Plasmodium species, previous works show that glycosylphosphatidylinositol anchor modifications, and to an unknown extent, a severely truncated N-glycosylation are the only glycosylation processes taking place in the parasite. Nevertheless, a detailed analysis of the parasite genome and the recent identification of the sugar nucleotide precursors biosynthesized by Plasmodium falciparum support a picture in which several overlooked, albeit not very prominent glycosylations may be occurring during the parasite life cycle. In this work, the authors review recent developments in the characterization of the biosynthesis of glycosylation precursors in the parasite, focusing on the outline of the possible fates of these precursors.